Detergents Destabilize the Cubic Phase of Monoolein. Implications for Membrane Protein Crystallization. - CAFFREY, MARTIN (Elsevier, 2003)
The in meso method for membrane protein crystallization uses a lipidic cubic phase as the hosting medium. The cubic phase provides a lipid bilayer into which the protein presumably reconstitutes and from which protein crystals nucleate and grow. The solutions used to spontaneously form the protein-enriched cubic phase often contain significant amounts of detergents that were employed initially to purify and to solubilize the membrane protein. By virtue of their surface activity, detergents have the potential to impact on the phase properties of the in meso system and, by extension, the outcome of the crystallization process. The purpose of this study was to quantify the effects that a popular series of nonionic detergents, the n-alkyl-b-D-glucopyranosides, have on the phase behavior of hydrated monoolein, the lipid upon which the in meso method is based. Phase identity and phase microstructure were characterized by small-angle x-ray diffraction on samples prepared to mimic in meso crystallization conditions. Measurements were made in the 0?408C range. Samples prepared in the cooling direction allow for the expression of metastability, a feature of liquid crystalline phases that might be exploited in lowtemperature crystallization. The results show that the cubic phase is relatively insensitive to small amounts of alkyl glucosides. However, at higher levels the detergents trigger a transition to the lamellar phase in a temperature- and salt concentrationdependent manner. These effects have important implications for in meso crystallization. A diffraction-based method for assaying detergents is presented.
PUBLISHED
Keywords: concentrationdependent; Biophysics